2019
DOI: 10.1590/2177-9465-ean-2018-0178
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Parents of Newborns in a Neonatal Intensive Care Unit

Abstract: Objective: To identify the level of stress and the most stressful situations for the parents of newborns hospitalized in a Neonatal Intensive Care Unit. Methods: A descriptive study, with a quantitative approach, performed with parents of newborns admitted to the Neonatal Intensive Care Unit. For the data collection, the Brazilian version of the Parental Stress Scale: Neonatal Intensive Care Unit (PSS: NICU) was used. The analysis was performed using descriptive statistics. Results: The change in the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 14 publications
(22 reference statements)
1
15
0
13
Order By: Relevance
“…When evaluating the stressors present in the NICU, a study showed that the altered maternal role, the baby's separation and helplessness were the main factors that led to an increase in stress levels in the parents. 12 These findings corroborate the present study that infers stress and its causes as one of the difficulties in the breastfeeding process.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…When evaluating the stressors present in the NICU, a study showed that the altered maternal role, the baby's separation and helplessness were the main factors that led to an increase in stress levels in the parents. 12 These findings corroborate the present study that infers stress and its causes as one of the difficulties in the breastfeeding process.…”
Section: Discussionsupporting
confidence: 91%
“…The literature points out the importance of investing in welcoming and harmonious environments to contribute to the mother's permanence in the NICU and, consequently, favoring the mother-baby bond and using proximity to promote MB. 12 Maintenance of lactation is also a challenge emphasized by mothers in this study. Due to the need for a zero diet to perform the surgeries, breastfeeding is interrupted and the drop in milk becomes insufficient, due to anxiety and concern about the child.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent study informs that allowing the family to place the NB in the kangaroo position from the first week of life, whether the baby is on mechanical ventilation or not, strengthens the bond and autonomy to care for the child; and preventing the mother from performing actions related to the maternal role generates feelings of loss of maternal function (29) . So, it is necessary to introduce, from the beginning of hospitalization, the family in care, regardless of the child's clinical conditions, using caution and common sense by the professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Provide the mother with the possibility of holding her baby in her womb in the first week of life, regardless of whether she is on mechanical ventilation or not, strengthens the mother-baby bond and encourages the woman to feel autonomous to take care of her child. Impairment in the actions of the mother's role, such as breastfeeding, changing diapers, bathing, hugging and kissing the child, causes feelings of loss of function in the mother, negatively impacting the mother-baby relationship (16) .…”
Section: Discussionmentioning
confidence: 99%